ABOUT WOOD’S PROFILED GRINDING - Bugayenko , Yaroslav (Forestry, Forest, Paper and Woodworking Industry, 2024)
In our case in order to receive good quality of the surface we used the sanding skin with grains no lower than №180. The quality of processed good didn’t depend on the direction of grinding against the fibers. In our opinion, the described scheme shows us how we can also successfully perform grinding of products with curved surfaces: borders, cornices, skirting, etc. You can also upgrade the machine installing mechanic feeder with automatic supply of products and by doing that you will decrease the labour costs.